2018
DOI: 10.2528/pierl18021908
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Surface Wall Suppression of Mutual Coupling Between Microstrip Patch Antenna Arrays for THZ-Band Applications

Abstract: This paper presents a novel 2D meta-surface wall to increase the isolation between microstrip patch radiators in an antenna array that is operating in the teraherz (THz) band of 139-141 GHz for applications including communications, medical and security screening systems. The metasurface unit-cell comprises conjoined twin 'Y-shape' microstrip structures, which are inter-digitally interleaved together to create the meta-surface wall. The proposed meta-surface wall is free of via holes and defected ground-plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…As well as, the minimum and average mutual coupling suppressions presented by this work show more than 22 and 28 dB improvements compared with Alibakhshikenari et al (2018). Here edge-by-edge distance between the radiation elements is 0.66λ 0 , but in Alibakhshikenari et al (2018) this parameter is 1.16λ 0 . One more point, regarding the different operating frequency bands the antenna arrays have different applications than each other.…”
Section: Radio Sciencementioning
confidence: 62%
See 1 more Smart Citation
“…As well as, the minimum and average mutual coupling suppressions presented by this work show more than 22 and 28 dB improvements compared with Alibakhshikenari et al (2018). Here edge-by-edge distance between the radiation elements is 0.66λ 0 , but in Alibakhshikenari et al (2018) this parameter is 1.16λ 0 . One more point, regarding the different operating frequency bands the antenna arrays have different applications than each other.…”
Section: Radio Sciencementioning
confidence: 62%
“…As advantages of the proposed work than Alibakhshikenari et al (2018) we can mention that the maximum mutual coupling suppression here by the proposed technique is 57 dB that shows more than 43 dB improvement than Alibakhshikenari et al (2018). As well as, the minimum and average mutual coupling suppressions presented by this work show more than 22 and 28 dB improvements compared with Alibakhshikenari et al (2018). Here edge-by-edge distance between the radiation elements is 0.66λ 0 , but in Alibakhshikenari et al (2018) this parameter is 1.16λ 0 .…”
Section: Radio Sciencementioning
confidence: 93%
“…In this respect, metasurfaces have been one of the techniques for suppressing mutual coupling between multiple antenna elements. [12][13][14][15]…”
Section: What Are Metasurfaces?mentioning
confidence: 99%
“…Mutual coupling induced by the surface current along the substrate and spatial electromagnetic fields, however, deteriorates the antenna radiation characteristics, and this is one of the major problems for antenna designers. In this respect, metasurfaces have been one of the techniques for suppressing mutual coupling between multiple antenna elements …”
Section: Introductionmentioning
confidence: 99%
“…The authors observed higher isolation between the transmitting and receiving antennas when using their novel isolation technique. In [13], the authors were able to achieve a suppression of more than 10 dB using a 2D metasurface wall with microstrip patch antennas. A reduction in the isolation of an airborne SAR system was explored in [14] using a simplified composite right-/left-handed transmission line (SCRLH-TL).…”
Section: Introductionmentioning
confidence: 99%